User Experience Analysis from User Centered Design Approach in Marketing Website - Adenia Kusuma Dayanthi; Eko Sediyono; Hendry Hendry (Universitas Multimedia Nusantara, 2023)
In the User Experience (UX) analysis carried out using the User Centered Design (UCD) approach, the research is based on user-oriented design. A website based on the UCD process will definitely generate high levels of satisfaction for its users. In this research, user experience analysis was conducted using a User Centered Design approach with Product Market Fit concept orientation. This concept is often ignored so that it becomes a major factor in the failure of a business start-up. The collection was carried out through several processes, namely in-depth interviews and distribution of questionnaires to a total of 30 respondents. The results of the questionnaire can be used as a reference to find out which aspects are good and which are still lacking. The aspect of displaying information on the monitor screen when opening a website gets the highest score of the other aspects with a percentage of 93% user satisfaction. The conclusion for each aspect states that the curious websites that are analyzed get a decent title.